2012
DOI: 10.1111/j.1756-2171.2012.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of learning by hiring on productivity

Abstract: This article focuses on the phenomenon of interfirm labor mobility as a potential channel for knowledge transfer. Using data from the Danish employer‐employee register covering the period 1995–2005, we investigate how knowledge carriers—technicians and highly educated workers recruited from a donor firm—contribute to knowledge diffusion and enhanced productivity in the hiring (recipient) firm. Structural estimation of the hiring firms' production functions shows that the impact of the recruitment of knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 22 publications
6
49
0
Order By: Relevance
“…Also, Kaiser et al (2015) and Braunerhjelm et al (2014) found a positive association between labour mobility and innovation, measured as patent applications. However, a negative relationship between innovation and mobility of highly qualified labour has also been established in previous literature (Balsvik 2011;Parrotta and Pozzoli 2012).…”
Section: Introductionmentioning
confidence: 63%
“…Also, Kaiser et al (2015) and Braunerhjelm et al (2014) found a positive association between labour mobility and innovation, measured as patent applications. However, a negative relationship between innovation and mobility of highly qualified labour has also been established in previous literature (Balsvik 2011;Parrotta and Pozzoli 2012).…”
Section: Introductionmentioning
confidence: 63%
“…13 Second, our interest in managers as workers who need specific skills and perform difficult tasks relates to the literature on trade and tasks (Blinder, 2006, Grossman andRossi-Hansberg, 2008). Third, the role played by workers' mobility across firms in our analysis contributes to the recent debate about the channels via which knowledge transfer takes place (Balsvik, 2011, Parrotta andPozzoli, 2012). Last, but not least, our wage analysis contributes to the literature devoted to explaining the determinants of managers' pay (Gabaix andLandier, 2008, Guadalupe andWulf, 2008), and to the literature that studies the internal organization of the firm and how this relates to a firm's characteristics such as export status .…”
Section: Introductionmentioning
confidence: 68%
“…Several recent empirical studies, including Gorg and Strobl (2005), Markusen and Trofimenko (2009), Balsvik (2011), Parrotta and Pozzoli (2012), and Stoyanov and Zubanov (2012), have documented the workings of this mechanism, linking firm productivity gains to hiring workers from technologically superior firms. 1 Since the latter receive no compensation from the firms that hire their workers, the existence of knowledge spillovers through worker mobility implies a positive externality.…”
Section: Introductionmentioning
confidence: 99%